Analysis of financial reports based on liquidity, solvency and profitability ratios to assess financial performance in cooperative konsumen dokma nahdlatul ulama sidoarjo university - Suci Lestari; Achmad Wicaksono (Institute of Computer Science (IOCS), 2023)
Financial reports are the final result of accounting activities. By having financial reports the company is able to see its financial position and financial performance periodically. This research aims to analyze the financial reports of the Cooperative Konsumen Dokma at Nahdatul Ulama Sidoarjo University using solvency, liquidity and profitability ratios. This research uses descriptive quantitative methods. The research data collected by researchers is in the form of secondary data, namely data in the Cooperative Financial Report from 2021-2022. The data obtained was analyzed descriptively. The research results show that the calculation of the profitability, solvency and liquidity ratios of the Dokma Cooperative for 2021-2022 obtained results above the established standards. This means that with the existing financial composition, the Cooperative has the ability to pay off its obligations and is also able to utilize existing assets to make a profit